Chromosomal aberrations and N-ras activation in human larynx carcinoma cell line Hep-2. (Baghdad Science Journal, 2025)
In the present study, cytogenetic and molecular techniques were conducted to detect the chromosomal aneuploidy and the involvement of N and H genes in squamous larynx carcinoma cell line Hep-2.Our results showed that numerical and structural abnormalities were involved in larynx cancer Hep-2.The total number of chromosomes ranging from tripolyploidy in passage187to more than that in passage207.The more frequent chromosomes involved in numerical aberrations were chromosomes1,7,16,17 and 18. Structural chromosomal aberrations were also detected.Deletion of short arm was detected in chromosome 1(del 1p) and the long arm of chromosome 1(del 1q)and 6(del 6q).Gaining on short arms were also recorded in chromosomes 3(3p+) and 12(12p+).At the molecular level,one allele of N-ras proto-oncogene was found deleted in the location 61 in passage 187 and complete deletion of both locations in passage 207.These findings reflex a great genomic instability in the the tumor model used in this study. Also the results confirmed the multistages theory in cancer arising.